USING GRACE AND GLDAS DRIVEN DATA TO ASSESS GROUNDWATER FLUCTUATIONS OF NIGER-SOUTH HYDROLOGICAL AREA OF NIGERIA - Uba,Uchechukwu Promise, Umeuduji, Joel E, Eludoyin, Olatunde Samuel (EPRA International Journal of Economic Growth and Environmental Issues(EGEI), 2023)
Gravitational Recovery and Climate Experiment’s Terrestrial Water Storage and Global Land Data Assimilation System’s Surface Water and Soil Moisture including Nigerian Hydrological Service Agency’s Groundwater Level were used to assess the temporal groundwater fluctuations of Niger-south Hydrological Area of Nigeria. The study adopted a cross-sectional research design; descriptive and inferential statistics was used for data analysis; Table was used for presentation. The study finds that there is no statistical significant difference between average monthly net recharge and average month storage changes at 95% probability level, it further concluded that the use of these satellites to acquire data and make decision will mark a new era and bring about fewer causalities on natural event(s), and therefore recommended us to take advantage of this free available resource to ameliorate challenges trying to extinct the existence of man from earth surface; therefore, increasing groundwater levels in Niger-south Hydrological Area needed to be properly managed because of rising groundwater flooding.